Reasons of the German legislator to remove the premise of sex difference to contracting marriage - RAKOCZY, TOMASZ (Prawo Kanoniczne, 2019)
From the October the 1st 2017 two people of the same sex can contract marriage in Germany. The key problem is that the German Constitution does not contain a legal definition of marriage. This legal fact opened discussion about model and subjects of marriage. Originally, both the Constitutional Court and the doctrine of German law stated that only a woman and man could contract marriage. Later, it was recognized that the constitutional provision only imposed on the state the obligation to protect marriage and the family, and thus the legislator was not entitled to define marriage in the scope of its members. The strict interpretation was chanced by certain judgments of the Tribunal and social events. In particular, the Court ruled on lame and heterosexual marriages as well as civil partnerships. He decided that they all do not fall within the definition of marriage, but that the legislator should provide them with legal protection. At the same time, a number of changes took place in society: the non-marital common life of free unions was accepted, and there was demand to end discrimination against homosexuals. For these reasons, the first law on civil unions was introduced in Germany. Subsequently, the same-sex premise in the Civil Code was introduced, creating the possibility of marriage for homosexuals. The existing legal status raises doubts as to compliance with the Constitution. However, there is no entity interested in submitting the application. The existing legal status also gives rise to ambiguities regarding the understanding of gender.